Faktor-Faktor yang Berhubungan dengan Kualitas Hidup Pasien Kanker: Factors Associated with the Quality of Life of Cancer Patients - Lina Dewi Anggraeni; Fransiska Novianty (Journal of Nursing Education and Practice, 2021)
Introduction: Cancer is a disease caused an abnormal cell growth due to the change in the expression of a gene, attacking cells or tissues to be around so that damage occurs. The condition can give a major change for the patient, either physically, psychologically, economically, or other. These changes can result in a decreased quality of life in people with cancer. Objectives: This study aims to identify the factors associated with quality-of-life patients with cancer. Method: This research is a quantitative study with a cross-sectional approach, using the WHOQOL-BERF questionnaire. The study was conducted from December 2017 to January  2018. Samples in this study were 33 respondents. Data analysis using chi-square and Kendall tau b. Result: The results of the bivariate analysis showed that family support had a significant relationship between the quality of life (P-value = 0.010), while age, sex, length of chemotherapy, level of education, and occupation did not significantly relate with quality of life. Conclusion: The recommendations of this study are health workers can provide support such as psychological counseling, nutrition, and pharmacology.